User testing a patient information resource about potential complications of vaginally inserted synthetic mesh - Nikolina Angelova; Louise Taylor; Lorna McKee; Naomi Fearns; Tracey Mitchell (BMC, 2021)
Abstract Background Vaginal mesh implants are medical devices used in a number of operations to treat stress urinary incontinence and pelvic organ prolapse. Although many of these operations have delivered good outcomes, some women have experienced serious complications that have profoundly affected their quality of life. To ensure that evolving patient information is up-to-date, accurate and appropriate, the Transvaginal Mesh Oversight Group 'user-tested' a newly developed Scottish patient resource, the first to focus exclusively on the issue of complications. The aim of this research was to gather feedback on usability, content, language and presentation to inform the development of the resource from a user perspective. Methods The experience of using the patient resource was captured through semi-structured interviews that followed a 'think-aloud' protocol. The interviewer observed each participant as they went through the resource, asking questions and making field notes. Participants' comments were then categorised using a validated model of user experience and subsequently analysed thematically. Results Thirteen people participated in the user testing interviews, including women with lived experience of mesh implants (n = 7), a convenience sample of staff working for Healthcare Improvement Scotland (n = 5) and a patient's carer (n = 1). The majority of participants considered the resource as clear and helpful. Respondents reported that some presentational aspects promoted usability and understandability, including the use of a font that is easy to read, bullet lists, coloured headings and simple language. Barriers included the reliance on some technical language and an explicit anatomical diagram. Participants endorsed the valuable role of health professionals as co-mediators of patient information. Conclusions The findings illustrate the value of undertaking in-depth user-testing for patient information resources before their dissemination. The study highlighted how the direct guidance or navigation of a patient information resource by a health professional could increase its salience and accuracy of interpretation by patients, their families and carers. These insights may also be useful to other developers in improving patient information.